How horror, mystery, and science fiction films construct femmes fatales: misogyny or empowerment? - Motlhamme, Jeffrey (My University, 2020)
I seek to investigate the representation of gender in film, particularly the ideological meaning of the femme fatale; what it represents. I want to also ask if it challenges the traditionally constructed ideas about gender in cinema? To comprehend the nature of this investigation, questions will be asked on what constitutes objectivization and misogyny on screen, and also importantly, what constitutes a femme fatale. The treating of females as objects, as an idea, shall be investigated in relation to the gaze. In this sense, I want to ask if the representation of the femme fatale is misogynistic or a source of empowerment? I employ a political philosophic interpretation or unmasking of the femme fatale, with a blend of feminist scholarship. I put four films in conversation with each other in an attempt to unmask the ideological meaning of the femme fatale. The films include My Cousin Rachel (2017), Audition (1999), Species (1995), and Species 2 (1998). The construction of the femme fatale in My Cousin Rachel (2017) is misogynistic because it promotes a view that male reasoning is superior to female reasoning. On an ideological level, the femme fatale in the film may be taken to represent a protest against naming and the patriarchal construction of social behaviour. Audition (1999) employs the femme fatale to serve as a violent attack on patriarchy. The femme fatale in Audition (1999) is presented as an obsessed torturer with a sense of madness attached to her. It is this madness; this other dark side of her that invalidates her resistance. Instead of deploying the femme fatale, Species 2 (1998) deploys a fatal man/homme fatale. Species 2 (1998) attempts to shift from patriarchal gender constructions by placing women in positions of power and highlighting issues around body politics in terms of sexual assault and abuse. Species (1995) reinforces the traditional gender constructions in a sense that it depicts women as the ‘objects of the gaze’ and men as the ‘bearers of the gaze’. The femmes fatales presented by the films in question are paranoid constructions with a surplus and excess attached to them. The fatal status of the femmes fatales is attached to them not so much because they cause harm to men, but because they are fundamentally fatal to the very order that empower men and oppress women; the patriarchal order. Less than the Gramscian notion of War of maneuver, the notion of War of position is appropriate in dealing with patriarchal cinema. One of the first and fundamental steps in challenging this male centred cinema is to recognize the material conditions of various groups. We have to interrogate the political economy of cinema in terms of who owns the means of production and who does not; the ones with power and the ones without. If the ideological power of the patriarchal cinema is not properly challenged at an ideological level, then cinema for women will always entail struggle.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts in Film and Television to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, 2020